PENYULUHAN PENTINGNYA PEMENUHAN GIZI BAGI IBU HAMIL DI DESA MINANGA TALLU KEC. SUKAMAJU KAB. LUWU UTARA TAHUN 2025 - Nurma; Zamli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Nutritional problems of pregnant women according to the 2020 Performance Accountability Report of the Ministry of Health of the Republic of Indonesia that are often encountered in pregnant women are chronic energy deficiency (CED). Anemia during pregnancy is a health problem that is often found in pregnant women that can cause complications in later pregnancy. According to WHO A pregnant woman is said to be anemic if she has a Hemoglobin level below 11 g / dl. Method: Socialization General explanation of the program to pregnant women and Counseling Providing Counseling about the importance of fulfilling nutritional needs and fluid intake in pregnant women. Results: This counseling activity was attended by Village Health Post Administrators, pregnant women and the surrounding community. The results of the counseling are: Increased level of knowledge in mothers, Able to apply and fulfill good nutritional needs needed during pregnancy, Pregnant women can know what nutrition is good during pregnancy. Nutrition for pregnant women is the nutritional needs that every pregnant woman needs to fulfill nutritional needs as a source of energy and energy in carrying out her daily activities. Adequate nutritional needs require adequate nutrients such as protein, carbohydrates, fats, folate, calcium, vitamin A, vitamin E, vitamin B1, iodine, and zinc. Adequate maternal nutrition during pregnancy impacts the growth and development of the fetus, therefore, pregnant women must consume healthy and nutritious foods.